A test generation strategy for pairwise testing. - Kuo-Chung Tai
Pairwise testing is a specification-based testing criterion which requires that for each pair of input parameters of a system, every combination of valid values of these two parameters be covered by at least one test case. The authors propose a novel test generation strategy for pairwise testing
Keywords: Input parameters; Pairwise testing; Software testing; Specification-based testing criterion; Test case; Test generation strategy; Valid values